The nutritive status of natural pastures on acid, leached soils in the Humansdorp area - Van der Merwe, F. J.(Francois Johannes),1932- (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc. Agric.) -- University of Stellenbosch, 1957.